EVOLUTION OF INDIAN VISUAL ARTS WITH FRESH PERSPECTIVES: A HISTORICAL ANALYSIS - Mishra, Sanjeev Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Paintings and sculptures are among the most sensitive and expressive forms of art, capturing human thoughts and emotions through the use of line, colour, and form. Long before recorded history—when early humans still lived in caves—they felt a deep need to express their creativity. They painted the walls of their rock shelters, driven by an innate sense of beauty and imagination. In Indian culture, the love for colour, pattern, and artistic expression is deeply rooted. Even during historical periods where we have limited documentation, Indians created vibrant drawings and paintings that reflect this enduring passion.